Investigation on bacterial biopolymers and biominerals for soil stabilization - Ramachandran, Asha Latha (Curtin University, 2021)
The practice of soil stabilization has become an essential part of present day geotechnical engineering projects. However, it is a matter of growing concern that popular chemical stabilizers possess high carbon footprint and adversely affect the eco-system. With the emergence of bio-geotechnology as an environmentally benign alternative to chemical stabilization, there is a paradigm shift in the field of soil stabilization. This thesis is a novel attempt to underpin the effect of bacterial biopolymers and biomineralisation on stabilization of soil.